Lymph node yield in gastrointestinal cancer surgery with or without prior neoadjuvant therapy: protocol for a systematic review and meta-analysis - Ronellenfitsch, Ulrich; Mathis, Nika; Friedrichs, Juliane; Kleeff, Jörg H. (JMIR Research Protocols, 2022)
cancer; chemotherapy; gastrointestinal cancer; lymph node harvest; lymph node yield; neoadjuvant chemotherapy; neoadjuvant radiotherapy; neoadjuvant therapy; resection; surgery